(untitled) (Sciental Journal of Education Humanities and Social Sciences, 2026)
The article examines the significance of ethical and moral foundations in enhancing women’s legal literacy. It emphasizes that legal awareness among women is not only shaped by formal laws and regulations but is also deeply influenced by ethical principles, moral values, and social norms that guide responsible behavior and civic engagement. The study explores how integrating ethical education, moral reasoning, and culturally informed approaches can strengthen women’s understanding of their rights, promote gender equality, and foster social responsibility. Furthermore, the article analyzes national and international frameworks that support women’s legal empowerment and evaluates strategies for effectively combining ethical, moral, and legal education. The findings suggest that a value-based and ethically grounded approach significantly improves women’s ability to apply legal knowledge in everyday life, enhancing both individual empowerment and broader societal development.